Implementation of FOC algorithm using FPGA for GaN-based three phase induction motor drive - Tung Duong Do Nam Duong Le; Vu Hoang Phuong; Nguyen Tung Lam (My University, 2022)
Implementation of FOC algorithm using FPGA for GaN-based three phase induction motor drive
Keywords: Thuật toán FOC; Công nghệ GaN; FPGA implementation